2022
DOI: 10.1097/aud.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Vestibular Assessment: Clinical Framework

Abstract: Objectives: Although vestibular deficits can have severe repercussions on the early motor development in children, vestibular assessment in young children has not yet been routinely integrated in clinical practice and clear diagnostic criteria to detect early vestibular deficits are lacking. In young children, specific adjustments of the test protocol are needed, and normative data are age-dependent as the vestibular pathways mature through childhood. Therefore, this study aims to demonstrate the feasibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Different protocols have been proposed to record c-VEMPs in children (12,13,(17)(18)(19)(20)22). However, their results are difficult to compare because some were obtained with BC stimulation and others with AC stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different protocols have been proposed to record c-VEMPs in children (12,13,(17)(18)(19)(20)22). However, their results are difficult to compare because some were obtained with BC stimulation and others with AC stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has even been reported that AC c-VEMPs can be recorded in term (17) and pre-term newborns (18), but not with a 100% success rate. BC c-VEMPs have been successfully used as a vestibular screening test in a large group of hearing-impaired infants tested at the age of 6 months (19) and the feasibility of BC c-VEMPs in a newborn hearing screening protocol has also been demonstrated (20). A decrease in AC c-VEMP amplitude response with age has been reported in healthy adult subjects (3,4,21), as well as in a wider population of 85 healthy participants (10 patients aged 10-19 years) for both AC and BC c-VEMP amplitude responses (16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vHIT maneuvres were performed with an amplitude between 10 and 20 degrees and peak velocity above 150 degrees per second. Gain values between 0.7 and 0.4 were considered mild lateral SCC dysfunction 32 and values below 0.4 were defined as severe impairment 10 . Saccular function was evaluated through bone‐conducted cVEMP measurements (Bio‐Logic Navigator‐Pro platform, Mundelein, IL, and Neuro‐Audio version 2010, Neurosoft, Ivanovo, Russia) using linear 500 Hz tone bursts presented at the mastoid at 59 dB HL (129 dB force level) intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Saccular function was evaluated through bone‐conducted cVEMP measurements (Bio‐Logic Navigator‐Pro platform, Mundelein, IL, and Neuro‐Audio version 2010, Neurosoft, Ivanovo, Russia) using linear 500 Hz tone bursts presented at the mastoid at 59 dB HL (129 dB force level) intensity. Rectified interpeak amplitudes below 0.3 (Bio‐Logic) or 1.3 (Neuro‐Audio) were classified as mild saccular dysfunction 32 . Severe saccular dysfunction was concluded if no reproducible cVEMP‐response could be elicited at all 10 .…”
Section: Methodsmentioning
confidence: 99%